Construções parentéticas encabeçadas por como no português - Silva, Diogo Oliveira da (2021)
This research investigates constructions headed by as/like/how in occurrences of the type as it is said, like you know, how is it called?, in the Lusophone varieties, in order to discuss its status under the focus of the Functional Discourse Grammar (FDG) by Hengeveld and Mackenzie (2008) and the Textual-Interactive Grammar (TIG) by Jubran (2006). For that, we raised the research questions: (i) how do the constructions headed by as/like/how work in the light of the FDG? (ii) what is the scope of as/like/how according to the FDG Interpersonal and Morphosyntactic Levels? (iii) in the light of TIG, are these constructions brackets? (iv) what is the syntactic ordering process for these constructions? As a general research aim, we seek to functionally describe the constructions initiated by as/like/how. As specific aims, we investigate: (i) the discursive, pragmatic and morphosyntactic properties of constructions initiated by as/like/how (HENGEVELD; MACKENZIE, 2008); (ii) the as/like/how status in these constructions (HENGEVELD; MACKENZIE, 2008); (iii) the syntactic ordering process of these constructions (HENGEVELD; MACKENZIE, 2008); and (iv) their bracketing functions in the discourse (JUBRAN, 2006). The methodology started from the following parameters, summarized here: 1) formal classification of as/like/how; 2) construction layer at the Interpersonal and Morphosyntactic Levels; 3) statute of as/like/how at the Interpersonal and Morphosyntactic Levels; 4) construction ordering and 5) identification of bracketing properties (formal constitution, boundary and function). The criteria were applied to occurrences found in the Lusophone Corpus of Spoken Portuguese, prepared by the Linguistics Center of the University of Lisbon (2009). We start from the assumptions of Stassi-Sé (2012), that the as/like/how, in these morphosyntacticaly independent constructions, works as a Function marker, and the constructions act as bracketing insertions, recurring from the Speaker's pragmatic and communicational intentions. The mentioned parameters helped to reach the final results: the constructions headed by as/like/how were framed as bracketing constructions in seven varieties of the Portuguese language, they are presented as Movements, composed of Discursive Acts, and as/like/how to act as a marker of Interactional functions, presenting Interactive functions Rescue and also Sharing (for Declarative illocutions), and the Interrogative illocutions constituted Interrogative Acts of content, with the item as/like/how working as a meditative question marker (FONTES, 2012), both acting in the monitoring verbal interaction. It is important to highlight the independence of the type of verbal construction (dicendi verbs, knowledge verbs, linking verbs and six other action verbs), to the declarative and interrogative Illocutions and the syntactic positioning of these Linguistic Expressions in Ppre (Pre-Orational Position). These characteristics lead us to observe the tendency of these constructions to act discursively, regardless of the semantic value attributed to the as/like/how traditionally. In these cases, we observed an emptying of meaning in this item, pointing to its grammaticalization process in the construction, whereas its performance in the scope of higher layers of the FDG Interpersonal Level.